0264 Probe: hazardous chemical products register for occupational use in belgium. (21st August 2017) - Godderis, Lode; Pauwels, Sara; Temmerman, Anne-Marie; Ronsmans, Steven; Schryver, Antoon De; Rusu, Dorina; Braeckman, Lutgart
Abstract : During their job, workers are exposed to a wide variety of working conditions including chemical substances that are potentially detrimental to employees' health. Today, Belgian data on occupational exposure to dangerous chemicals are collected by Occupational Health Services (OHS) merely for the purpose of assuring the appropriate health screening. This makes these data of little use for epidemiological research and exposure surveillance on one hand and for policy development by competent authorities on the other hand. The PROBE (Hazardous chemical P roducts R egister for O ccupational use in Be lgium) study is set up to investigate the exposure of Belgian workers to dangerous chemical products, including type, duration and frequency of exposure. PROBE consists of a systematic collection and analysis of occupational chemical exposure data. A trained, motivated, and representative sample of occupational physicians from both internal and external OHS will be invited to participate. The data will be collected on a regular basis over a period of 5 months. Besides demographics, exposure measurements and health related data will be collected. First, a pilot will be kicked off in a limited sample of occupational physicians, testing the feasibility of the program. The final goal of the project is to register in a comprehensive but easy way the exposure to dangerous chemicals in order to improve preventive measures, to ensure workers' health and to develop a national surveillance policy.